Pentingnya Gaya Komunikasi dalam Kepemimpinan - Tasya; Hidayat, Nurul; Lukman, Lukman (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2023)
Communication styles can be used to motivate employees in terms of improving performance. The communication style used by leaders is adapted to the situation and conditions of the institution or organization. The purpose of this research is to find out how important communication style is and the type of communication style used by a leader, be it an organizational leader, a leader in an agency or institution, a leader in society, and so on. The research method used is a qualitative method in the form of a literature study. Data was taken from the Publish or Perish application, totaling 10 articles related to the communication styles used by leaders in leading organizations, agencies and so on. The results of this research are the communication style. The equalitarian style is considered the most effective communication style to use for a leader.